Perencanaan Sistem Perpipaan Pemadam Kebakaran pada Galangan Kapal dengan Luas Area 114.389 m2 - Tubuh Pierehanto; annas Firmansyah; Projek Priyonggo Sumangun L; Lely Pramesti (Proceedings Conference on Marine Engineering and its Application, 2023)
Fires can occur anywhere and anytime, including shipyards. Fires in shipyards can cause companies to incur repair costs, recover company assets, and provide insurance for victims. The existing extinguishing system is still simple and does not cover the entire area. Therefore, it is necessary to plan a fire extinguishing system with NFPA and SNI standards that can cover all areas of the company. The initial planning step is to design the pipeline system, then select pumps, calculate pipe support requirements, and calculate estimated material costs. This research resulted in a total head using pipe flow expert software of 210.114 m. The percentage of errors between manual calculations and software is 3.363%. The need for pipe support for an 8-inch pipe requires a minimum of 1 support, while a 6-inch pipe requires a minimum of 71 supports. So, theestimated cost of materials and equipment in this plan is IDR 3,443,630,750.